2012
DOI: 10.1002/jor.22061
|View full text |Cite
|
Sign up to set email alerts
|

The effects of denervation, reinnervation, and muscle imbalance on functional muscle length and elbow flexion contracture following neonatal brachial plexus injury

Abstract: The pathophysiology of paradoxical elbow flexion contractures following neonatal brachial plexus injury (NBPI) is incompletely understood. The current study tests the hypothesis that this contracture occurs by denervation-induced impairment of elbow flexor muscle growth. Unilateral forelimb paralysis was created in mice in four neonatal (5-day-old) BPI groups (C5-6 excision, C5-6 neurotomy, C5-6 neurotomy/repair, and C5-T1 global excision), one non-neonatal BPI group (28-day-old C5-6 excision), and two neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 33 publications
10
71
2
1
Order By: Relevance
“…Nikolaou has shown that functional shortening of denervated muscle plays a primary role in contracture pathogenesis [32]. However, the mechanism of contracture development in denervated muscle remains unanswered [33,34].…”
Section: Natural Historymentioning
confidence: 99%
“…Nikolaou has shown that functional shortening of denervated muscle plays a primary role in contracture pathogenesis [32]. However, the mechanism of contracture development in denervated muscle remains unanswered [33,34].…”
Section: Natural Historymentioning
confidence: 99%
“…Clinical studies have also demonstrated the effect of peripheral nerve system on bone growth [44,45]. In 2012 Reading et al [44] retrospectively reviewed children with neonatal brachial plexus palsy who had underwent joint rebalancing with magnetic resonance imaging (MRI).…”
Section: Results Of Denervation In Growing Limbsmentioning
confidence: 99%
“…The leading explanation is "muscle imbalance", involving preferential flexor action [8], secondary to delayed reinnervation of the elbow extensors vs the flexors [10]. This hypothesis does not account for cases with flexion paralysis [11].…”
Section: Discussionmentioning
confidence: 99%
“…The historical [8] clinical hypothesis for EFC is delayed elbow extensor reinnervation vs the flexors [10], allowing preferential flexor action for a brief period. However, EFC occurs even in cases without recovery of elbow flexion [11]. Additional hypotheses include: long head of biceps over-activity [12], uncommon C8-T1 pattern injuries [13], presence of shoulder contracture [14], and abnormal posturing [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation